A new methodology to determine the design sensitivity of critical automotive body joints for basic design cycle. (September 2019) - Tunç, Birkan; Şendur, Polat
As a result of more stringent requirements for improved fuel economy and emissions, there has been an increasing research activity to make vehicles lighter weight under some predetermined structural performance targets such as the stiffness of the vehicle body. The vehicle body structure is one of the most significant contributors to the weight of an automotive. Therefore, understanding the automotive joint properties on vehicle body performance is of significant importance as they are closely linked to structural integrity and weight of the vehicle body. In this paper, we develop a new methodology to quantify the sensitivity of critical joints of an automotive on the key performance indices. Torsional stiffness is chosen as static key performance index, while vehicle body modes are selected as dynamic key performance indices. Lower and upper sections of the A-pillar, B-pillar, C-pillar, and D-pillar of an automotive body are replaced by bushing elements having appropriate stiffness properties in the simplified model. Stiffness of bushing elements is tuned by minimizing the error between the original and simplified models on the aforementioned key performance indices. Once a satisfactory correlation is achieved between the simple model and the original model, bushing stiffness for each section is varied to determine the sensitivity of each joint. The proposed approach is demonstrated on a finite element model of 2010 Toyota Yaris. Finally, a design study is presented to improve the body key performance indices using the sensitivity results. The simulation results show that the methodology has a potential for the basic design cycle, where the targets for section properties need to be defined and at later design cycles, where the joints can be realized in design using the sensitivity of joints resulting in more efficient body structure considering the trade-offs between structural integrity and weight.